Численный анализ силового контактного взаимодействия бурового долота с породой - Кущ, В.И.; Казьмин, А.О. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
An advanced approach has been suggested for evaluating contact pressure on the drilling bit surface, based on the finite–element analysis of model boundary value problem of bit–rock contact interaction. The calculated from numerical simulations variation of wear intensity over the drilling bit surface is fairly close to that observed in a practice, which is a solid argument in a favour of adequateness of the proposed mathematical model and reliability of reported numerical data.